Full-Potential Electronic Structure Method Energy and Force Calculations with Density Functional and Dynamical Mean Field Theory - Wills, John M.; Alouani, Mebarek; Andersson, Per.; Delin, Anna.; Eriksson, Olle.; Grechnyev, Oleksiy; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book covers the theory of electronic structure of materials, with special emphasis on the usage of linear muffin-tin orbitals. Methodological aspects are given in detail as are examples of the method when applied to various materials. Different exchange and correlation functionals are described and how they are implemented within the basis of linear muffin-tin orbitals. Functionals covered are the local spin density approximation, generalised gradient approximation, self-interaction correction and dynamical mean field theory.
Formalisms -- Introductory Information -- Density Functional Theory and the Kohn–Sham Equation -- Consequences of Infinite Crystals and Symmetries -- to Electronic Structure Theory -- Linear Muffin-Tin Orbital Method in the Atomic Sphere Approximation -- The Full-Potential Electronic Structure Problem and RSPt -- Dynamical Mean Field Theory -- Implementation -- Obtaining RSPt from the Web -- Applications -- Total Energy and Forces: Some Numerical Examples -- Chemical Bonding of Solids -- Magnetism -- Excitated State Properties -- A Database of Electronic Structures -- Future Developments and Outlook.
Keywords: Condensed matter; Physics; Condensed Matter Physics; Mathematical Methods in Physics